SYNTHESIS AND ANTIMICROBIAL SCREENING OF 2,6-DIAMINOPYRIDINE SCHIFF BASES OF ISATIN DERIVATIVES - SHRIVASTAVA, SHOBHIT; AHUJA, DHARMENDRA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Synthesis and in vitro antimicrobial screening of 2,6-diaminopyridine Schiff bases of isatin derivatives. Methods: Isatin and it’s 5-substituted derivatives (S1-5) were prepared by Sandmeyer method and N2-Benzylidenepyridine-2,6-Diamine (M) was obtained by the reacting 2,6-diaminopyridine with benzaldehyde. Schiff bases (MS1-5) were prepared by reacting isatin derivatives (S1-5) with N2-Benzylidenepyridine-2,6-Diamine (M). Resultant compound structures were confirmed by some analytical techniques’ data. All synthesized compound were screened for in vitro antimicrobial activity by broth dilution methods against Staphylococcus aureus (MTCC-3160), Bacillus subtilus (MTCC-441), Escherichia coli (MTCC-452), Klebsiella pneumoniae (MTCC-432), Candida albicans (MTCC-183), Aspergillus flavus (MTCC-277) using ciprofloxacin and fluconazole as standard drugs. Results: All compounds exhibited better antibacterial activity compared to standard. Among all compounds, MS2 and MS4 were found most effective against all strains of bacteria. Only MS3 and MS5 showed antifungal activity against both fungal strains. Conclusion: All newly synthesized Schiff bases of isatin showed significant antibacterial activity against the tested strain of bacteria, only a few compounds were found effective as antifungal.